Estrutura populacional de Jacaratia spinosa (Aubl.) A. DC. (CARICACEAE) no Parque Estadual de Vila Rica do Espírito Santo (Fênix, PR, Brasil) - Assad Filho, Nabi (2001)
The present study refers to the survey of the population structure of Jacaratia spinosa, in the riparian forest of the Ivaí River, located in the State Park of Vila Rica do Espírito Santo, Municipality of Fênix, PR. Sampling was carried out from May to June 2001, in an area of 1ha, divided into 25 plots of 20m x 20m. Forty-five individuals were sampled, 20 young and 25 juveniles/adults, distributed mainly in the range from 40 to 100 m from the river bank. Cluster analysis indicated the existence of four groups, related to the density of juveniles and juveniles/adults, per plot and the Spearman correlation test showed that the groups of juveniles are independent of the distance with the juveniles/adults. Higher percentages of number of individuals were verified in the lower classes of diameter and height.